Reconceptualising fictional (un)reliability and (un)trustworthiness from a multidisciplinary perspective: categories, typology and functions - Nünning, Vera (Unreliable narration and trustworthiness, 2015)
Das Kapitel Reconceptualising Fictional (Un)reliability and (Un)trustworthiness from a Multidisciplinary Perspective: Categories, Typology and Functions erschien in Unreliable Narration and Trustworthiness auf Seite 83.